Customer identity concealing and insider selling profitability: Evidence from China - Huang, Wan; Bai, Yufan; Luo, Hong (Journal of Corporate Finance, 2024)
This study investigates whether insiders exploit the information advantage arising from customer identity concealment to profit from selling their shares. We examine this issue in the context of China, given the voluntary nature of customer information disclosure there. We find that insider selling profitability is significantly greater when firms conceal customer identities than when they disclose them, especially when customer identities are more informative. We also find evidence of significant trading profitability for both insiders and their relatives, as well as both core and general executives. Furthermore, we find that the results are weaker for firms with more effective internal monitoring and those with more attention from sophisticated market participants but are stronger for firms with more information disclosure manipulation. These findings are consistent with the hypothesis that insiders opportunistically trade on customer-related private information rather than unintentionally sell shares. In additional tests, we find that insiders deliberately conceal customer identities in response to their personal trading incentives, indicating that insiders may increase their information advantage through strategic customer information disclosure. Overall, our research sheds light on the black box of information sources of insider trading from the perspective of supply chains and the insider trading incentives behind firms' concealment of customer identities.